2013
DOI: 10.3390/ph6101322
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Response to Long-Term Infliximab Therapy in Children with Crohn’s Disease

Abstract: Secondary loss of response (LoR) often precludes further use of infliximab in children with Crohn’s disease. Immunomodulators may reduce the incidence of LoR but their combination with infliximab presents safety concerns. We aimed to determine the long-term durability of infliximab response in paediatric Crohn’s, effect of immunomodulators on LoR, and secondarily the effect of infliximab on growth. We retrospectively audited patients on maintenance infliximab at a single centre. Data included height and weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…On the other hand, it is to be considered that combination therapy is associated with the risk of increased toxicity. Moreover, based on the reports on hepatosplenic T-cell lymphoma (HSTCL, see section 'Safety of ADA') in predominantly young male patients on combination therapy, many pediatric gastroenterologists converted to anti-TNF-a monotherapy after a short duration of combination therapy, or combined therapy with MTX (instead of a thiopurine) [40].…”
Section: Combination Therapy With Immunomodulators Versus Monotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it is to be considered that combination therapy is associated with the risk of increased toxicity. Moreover, based on the reports on hepatosplenic T-cell lymphoma (HSTCL, see section 'Safety of ADA') in predominantly young male patients on combination therapy, many pediatric gastroenterologists converted to anti-TNF-a monotherapy after a short duration of combination therapy, or combined therapy with MTX (instead of a thiopurine) [40].…”
Section: Combination Therapy With Immunomodulators Versus Monotherapymentioning
confidence: 99%
“…The fully human nature of ADA is thought to be associated with a lower risk of formation of antibody against anti-TNF-a, thus reducing the risk of infusion reactions, delayed hypersensitivity reactions and decreased serum drug levels leading to a shorter duration of response, as usually observed with IFX due to its chimeric nature [40,41].…”
Section: Immunogenicity Of Adamentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-TNF agents have a promising potential for improving growth as they were shown to induce prompt mucosal healing [110,111], reverse the pro-inflammatory cytokines cascade [113] and enable prolonged corticosteroid withdrawal [108][109][110]. Indeed, numerous studies suggest an increase in height velocity and height z-score following prolonged anti-TNF treatment, providing treatment is undertaken early enough prior to or during puberty [4,106,111,112,[114][115][116][117][118][119][120]. In contrast, Sinitsky et al [121] reported a significant improvement in BMI z-score at one year of treatment with IFX in children with CD but failed to show significant changes in height velocity.…”
Section: Biologic Treatmentmentioning
confidence: 99%
“…It is believed that the most likely cause of secondary loss of response is the development of antibodies to the biologic agent. Concomitant therapy with an immunosuppressant appears likely to reduce the chances of antibody development, [111][112][113] but this practice has been complicated by the recognition of the potential increased risk of development of malignancy, especially hepatosplenic T-cell lymphoma (HSTCL). HSTCL is a rare and usually fatal lymphoma reported in association with past use of thiopurines, either alone or in combination with infliximab or adalimumab.…”
mentioning
confidence: 99%